Effect of Different Mineralizers in the Sonochemical Synthesis of Self-Assembled Nanorods Vanadium Oxide - Taufiq-Yap, Y.H.; Hoh, J.R. Joshua; Wong, Y.C. (Asian Journal of Chemistry, 2010)
The effects of different potassium salts (KNO3 and KCl) as mineralizer on the synthesis of self-assembled nanorods vanadium pentoxide, V2O5 via sonochemical treatment were studied at different duration i.e., 30, 60, 90 and 120 min. All the materials synthesized were further characterized by x-ray diffraction, scanning electron microscopy and transmission electron microscopy. X-ray diffraction patterns revealed that the potassium ion from the mineralizers reacted with the V2O5 after prolonged sonochemical treatment duration. The morphology of the V2O5 changed from platelet-like structures into nanorods after 90 min of sonochemical treatment. TEM micrographs show the process of formation of the self-assembled V2O5 nanorod bundles with increased sonochemical treatment duration.